Early Marriage Situation of Ethnic Adolescent Girls in Xiengnguen District, Luang Prabang Province - Yang, Ye; PHAIGNAVONG , Somchay; KHOTSAIGNO , Saiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study intended to investigate the situation of economic, education, culture and attitude of ethnic adolescent girls, parents, local customary law leaders and village authorities toward early marriage among Hmong and Khmu ethnic groups in Xiengnguen District, Luang Prabang Province, Data and information were collected via semi-structured interviews questionnaires, by using purposive sampling targeted a total of 44 samplings. The quantitative data were analyzed by using Microsoft Excel and SPSS program in percentage and the qualitative information was consolidated from all responses. The key findings revealed that most adolescent girls viewed early marriage as a way to pursue independence and a better life. Anyhow, getting marriage at young age has tendency to have many children, put girls’ health at risks and trapped in poverty. evidence indicated that all ethnic adolescent girls in the two target villages relied on doing farming, their average annual income was approximately 27 million Lao Kip and was insufficient for the basic needs, In summary, parents, customary leaders, and village authorities strongly reject early marriage notion, viewing it as an inappropriate practice that fails to preserve cultural tradition. Moreover, it was not aligned with with Lao PDR legal frameworks, the findings also highlighted that early marriage imposes significant burdens to the family and put substantial anxiety for both parents and parent-in laws.